Tracking Performance Studies Graduates Semarang Health Polytechnic, Ministry of Health - Supriyana Supriyana; Warijan Warijan; Arwani Arwani (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
The aim of the research was to survey about the graduate's working appearance based on his / her leader and colleague including the integrity capacity, communication, competency, information and technology, partnership, and self development. A quantitative research by applying survey was conducted to 42 samples (21 leaders and 21 colleagues) gained from 21 users. Research results showed that by enlarge the capacity of integrity, communication, competency, information and technology, partnership, and self development of the graduates were in good category resulted of mean score ranging from 2.57 – 3.14. However, the capability to communicating in English actively, browsing internet, being a team motivator, and involving in profession / community organization were in poor category.